1995
DOI: 10.1111/j.1442-200x.1995.tb03678.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐conventional portosystemic shunts in children with extrahepatic portal vein obstruction

Abstract: Portal hypertension due to extrahepatic portal vein obstruction is ideally treated by the use of a selective shunt. In a four year period between July 1987 and June 1992, 50 surgical procedures were carried out in 48 children with portal hypertension‐related variceal hemorrhage. The portal, splenic, mesenteric, or coronary vein was not available for anastomosis in four children who, therefore, underwent non‐conventional shunts which are described here. There was no postoperative mortality. One patient had a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…When the thrombus extends along the portosplenic axis, the chief route of decompression of the fundal gastric varices the splenic vein, is blocked; splenorenal shunts are not possible and a shunt with a superior mesenteric vein or its branch, even if patent, will not achieve decompression of gastric varices. Unorthodox shunts though occasionally successful [12] have a high failure rate [13]. Even if the shunt remains patent, adequate decompression through the small collateral does not take place [12], as was seen in one patient in this series.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…When the thrombus extends along the portosplenic axis, the chief route of decompression of the fundal gastric varices the splenic vein, is blocked; splenorenal shunts are not possible and a shunt with a superior mesenteric vein or its branch, even if patent, will not achieve decompression of gastric varices. Unorthodox shunts though occasionally successful [12] have a high failure rate [13]. Even if the shunt remains patent, adequate decompression through the small collateral does not take place [12], as was seen in one patient in this series.…”
Section: Discussionmentioning
confidence: 62%
“…Unorthodox shunts though occasionally successful [12] have a high failure rate [13]. Even if the shunt remains patent, adequate decompression through the small collateral does not take place [12], as was seen in one patient in this series.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The non-selective portosystemic shunts, such as mesocaval, portocaval or central splenorenal shunt, adequately decompress the portal circulation, but because they are considered major surgical procedures, they are not commonly used nowadays. Also, non-conventional portosystemic shunts using large collateral vessels may be performed in patients with EPVO, for example, children with extensive thrombosis of the portal venous system [ 90 ].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In case of extensive thrombosis of the portal venous system, nonconventional portosystemic shunts using large collateral vessels may be performed. 30 There are no data available regarding the use of ␤ adrenergicblockers or nitrates in the long-term management of patients with ectopic varices. A meta-analysis of randomized, controlled trials comparing a nonselective ␤-blockade versus placebo showed the efficacy of ␤-blocker therapy for secondary prophylaxis of bleeding from esophagogastric varices.…”
Section: Management Of Bleeding Ectopic Varicesmentioning
confidence: 99%